Spexin Suppress Food Intake in Zebrafish: Evidence from Gene Knockout Study. Issue 1 (December 2017) - Zheng, Binbin; Li, Shuisheng; Liu, Yun; Li, Yu; Chen, Huapu; Tang, Haipei; Liu, Xiaochun; Lin, Haoran; Zhang, Yong; Cheng, Christopher
Abstract Spexin1 (SPX1) is a newly discovered neuropeptide in vertebrates. Its biological function remains to be elucidated. In this study, we have generated the zebrafishspx 1−/− mutant lines using transcription activator-like effector nucleases. Phenotypes of thespx1 −/− mutant zebrafish were analyzed in order to understand the effects on reproduction and food intake. The reproductive capability is not impaired inspx1 mutant zebrafish. However, we found that thespx1 −/− mutant fish had a higher food intake than the wild type (WT) fish. Real-time PCR revealed that the expression level of agouti-relate protein 1 (AgRP1), a significant appetite stimulant, was significantly higher inspx1 −/− mutant fish after feeding. Intracranial administration of SPX1 could also reduce the mRNA expression of the AgRP1. These data suggest that SPX1 might decrease the food intake by down regulating the expression level ofagrp1 . Furthermore, spx1 −/− mutant fish exhibited higher glucose, triacylglycerol and cholesterol in the serum than WT fish. However, the hyperphagia did not lead to a higher growth rate or body fat percentage. Taken together, our study suggests that SPX1 may serve as a satiety signal molecular by suppressing the AgRP1 in the brain.